LINC01140 Regulates Radiosensitivity of Nasopharyngeal Carcinoma Cells Through the ceRNA Network : LINC01140 regulates radiosensitivity of NPC cells - Li, Jia; Li, Yan; Liu, Liang; Wu, Dan; Yang, Tao; Fan, Yuwei (Cellular and Molecular Biology, 2022)
Nasopharyngeal carcinoma (NPC) is one of the most lethal head and neck cancers, threatening the health of people across the globe, especially in East and Southeast Asia, the Arctic, the Middle East and North Africa. Long non-coding RNAs (lncRNA) have been reported to regulate multiple cancers, including NPC. However, the role of LINC01140 in NPC remains to be covered. In this study, we found that LINC01140 is downregulated in NPC cells. It was uncovered from functional assays that LINC01140 inhibits the proliferation and improves the apoptosis and radiosensitivity of NPC cells. The downstream mechanism by which LINC01140 exerted its functions was explored in subsequent. As proven by mechanism experiments, cytoplasmic LINC01140 positively regulated the expression of ZNF621 through competitively binding to miR-452-5p. ZNF621 can also enhance the radiosensitivity of NPC cells. To summarize, LINC01140 regulates the radiosensitivity of NPC cells through the competing endogenous RNA (ceRNA) mode. Our study aims to identify novel biomarkers for regulating the radiosensitivity of NPC.